2018 Alzheimer's disease facts and figures (Alzheimer's & dementia, 2018)
This article describes the public health impact of Alzheimer's disease (AD), including incidence and prevalence, mortality and morbidity, costs of care, and the overall impact on caregivers and society. The Special Report examines the benefits of diagnosing Alzheimer's earlier in the disease process, in the stage of mild cognitive impairment due to Alzheimer's disease. An estimated 5.7 million Americans have Alzheimer's dementia. By mid-century, the number of people living with Alzheimer's dementia in the United States is projected to grow to 13.8 million, fueled in large part by the aging baby boom generation. In 2015, official death certificates recorded 110,561 deaths from AD, making AD the sixth leading cause of death in the United States and the fifth leading cause of death in Americans age ≥65 years. Between 2000 and 2015, deaths resulting from stroke, heart disease, and prostate cancer decreased, whereas deaths from AD increased 123%. In 2017, more than 16 million family members and other unpaid caregivers provided an estimated 18.4 billion hours of care to people with Alzheimer's or other dementias. This care is valued at more than $232 billion, but its costs extend to family caregivers' increased risk for emotional distress and negative mental and physical health outcomes. Average per-person Medicare payments for services to beneficiaries age ≥65 years with Alzheimer's or other dementias are more than three times as great as payments for beneficiaries without these conditions, and Medicaid payments are more than 23 times as great. Total payments in 2018 for health care, long-term care and hospice services for people age ≥65 years with dementia are estimated to be $277 billion. With the identification of AD biomarkers in recent years, our understanding of the disease has moved from one based on symptoms to one based on brain changes. Because these changes begin well before clinical symptoms arise, Alzheimer's has the potential to be diagnosed before the dementia stage. Early diagnosis of AD could have important personal and financial benefits. A mathematical model estimates that early and accurate diagnosis could save up to $7.9 trillion in medical and care costs.